Towards devising a fund management system using blockchain - Bente Rashid, Nibula; Saha, Joyeeta; Prova, Raonak Islam; Tasfia, Nowshin; Shanto, Md. Nazrul Huda (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.